Estimating the burden of hyperkalaemia in the UK in high-risk patient populations. (25th November 2020) - McEwan, P; Hoskin, L; Badora, K; Sugrue, D; James, G; Hurst, M; Tafesse, E
Abstract: Background: Patients with chronic kidney disease (CKD), heart failure (HF), resistant hypertension (RHTN) and diabetes are at an increased risk of hyperkalaemia (HK) which can be potentially life-threatening, as a result of cardiac arrhythmias, cardiac arrest leading to sudden death. In these patients, renin-angiotensin-aldosterone system inhibitors (RAASi), are used to manage several cardiovascular and renal conditions, and are associated with an increased risk of HK. Assessing the burden of HK in real-world clinical practice may concentrate relevant care on those patients most in need, potentially improving patient outcomes and efficiency of the healthcare system. Purpose: To assess the burden of HK in a real-world population of UK patients with at least one of: RHTN, Type I or II diabetes, CKD stage 3+, dialysis, HF, or in receipt of a prescription for RAASi. Methods: Primary and secondary care data for this retrospective study were obtained from the UK Clinical Practice Research Datalink (CPRD) and linked Hospital Episode Statistics (HES). Eligible patients were identified using READ codes defining the relevant diagnosis, receipt of indication-specific medication, or, in the case of CKD, an estimated glomerular filtration rate (eGFR) ≤60 ml/min/1.73m 2 within the study period (01 January 2008 to 30 June 2018) or in the five-year lookback period (2003–2007). The index date was defined as 01 January 2008 or first diagnosis of an eligible condition or RAASi prescription, whichever occurred latest. HK was defined as K+ ≥5.0 mmol/L; thresholds of ≥5.5 mmol/L and ≥6.0 mmol/L were explored as sensitivity analyses. Incidence rates of HK were calculated with 95% confidence intervals (CI). Results: The total eligible population across all cohorts was 931, 460 patients. RHTN was the most prevalent comorbidity (n=317, 135; 34.0%) and dialysis the least prevalent (n=4, 415; 0.5%). The majority of the eligible population were prescribed RAASi during follow-up (n=754, 523; 81.0%). At a K+ threshold of ≥5.0 mmol/L, the dialysis cohort had the highest rate of HK (501.0 events per 1, 000 patient-years), followed by HF (490.9), CKD (410.9), diabetes (355.0), RHTN (261.4) and the RAASi cohort (211.2) (Figure 1). This pattern was still observed at alternative threshold definitions of HK. Conclusion: This large real-world study of UK patients demonstrates the burden of hyperkalaemia in high-risk patient populations from the UK. There is a need for effective prevention and treatment of HK, particularly in patients with CKD, dialysis or HF where increased incidence rates are observed which in turn will improve patient outcomes and healthcare resource usage. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): AstraZeneca